New On-Water Test for the Assessment of Blood Lactate Response to Exercise in Elite Kayakers. Issue 12 (December 2019) - PILOTTO, ANDREA M.; RASICA, LETIZIA; SCALISE, GABRIELE; ANNONI, STEFANO; LA TORRE, ANTONIO; MARZORATI, MAURO; PORCELLI, SIMONE
ABSTRACT: Purpose: Lactate thresholds are physiological parameters used to train athletes and monitor performance or training. Currently, the assessment of lactate thresholds in kayakers is performed in a laboratory setting utilizing specific ergometers; however, laboratory tests differ from on-water evaluation for several reasons. The aim of this study was to assess reliability and validity of a new on-water incremental test for the assessment of blood lactate response to exercise in flat-water kayakers. Maximal lactate steady state test (MLSS) was used as criterion measurement. Methods: Eleven junior (16.5 ± 1.9 yr) élite flat-water kayakers performed: i) an incremental cardiopulmonary test up to voluntary exhaustion on a stationary kayak ergometer to determine peak oxygen uptake; ii) an on-water 1000‐m distance trial (T1000) to record best performance time and average speed ( S 1000 ); iii) two repetitions of on-water incremental kayaking test (WIK test); iv) several repetitions of on-water constant speed tests to determine MLSS. Speed, HR, and blood lactate concentrations were determined during on-water tests. Results: The best performance time in T1000 was 262 ± 13 s, corresponding to an S 1000 of 3.82 ± 0.19 m·s −1 . Lactate threshold determined by modified D max method (LTDmod ) during WIK test was 2.78 ± 1.02 mmol·L −1 and the corresponding speed ( S LT ) was 3.34 ± 0.16 m·s −1 . Test–retest reliability, calculated on S LT, was strong (ICC = 0.95 and r = 0.93). MLSS test corresponded to 3.06 ± 0.68 mmol·L −1 and was reached at a speed ( S MLSS ) of 3.36 ± 0.14 m·s −1 . Correlation coefficient between S LT and S MLSS was 0.90 ( P = 0.0001). Interestingly, a significant correlation ( r = 0.96, P < 0.0001) was observed between S LT and S 1000 . Conclusions: The WIK test showed good reliability and validity for the assessment of speed corresponding to LTDmod in flat-water kayakers and it could be a useful tool to monitor athletic performance. The speed value at LTDmod nicely predicted performance on 1000 m.